Allopathic Effect of Acacia seyal (Talih) on Germination and Seedling Growth of Sorghum bicolor (Sorghum) - , Fatima A. Hassan, Mai M. A. Hassan, Imad-Eldin A. Ali Babiker (Archives of Current Research International, 2018)
Acacia seyal is a multipurpose tree that can be used as Agro-forestry species. In order to ascertain its suitability to this practice an experiment was carried out to investigate the allelophatic effect of Acacia seyal on the Sorghum seeds germination. The experiment was conducted at the controlled germination chamber. The treatments used irrigation of two varieties of, Sorghum bicolor seeds namely HSD and Tabat. Seeds of both varieties were irrigated with Acacia seyal water extracts from roots (R), leaves (L), parks (P) and combinations of R+L, R+P, P+L and R+L+P and in control treatment no extract used. The experiment arranged in a Complete Randomized Block Design (CRBD) with four replication. The results on variety Tabat showed that all parts of the tree affected significantly (p≤ .0.0007) the Sorghum germination, particularly the leaves & Root combination extract (31.75%) and the combination of the all parts together (23.8%). The germination of variety HSD was not significantly (p≤ .0.1) affected by the different extracts used.